Single-phase grid-connected power control in dq synchronous reference frame with space vector modulation using FPGA - Ali Salam Al-Khayyat; Amean Al-Safi; Mustafa Jameel Hameed (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
This paper presents the performance of controlling the active and reactive power of single-phase grid connected inverter by dq synchronous reference frame and space vector modulation (SVM) which is implemented by using field programmable gate array (FPGA) due to the flexibility they offer in comparison to other digital signal processors, hence it become the standard instruments for implementing various types of pulse width modulation (PWM) digital signal processors (DSPs). The SVM method has used because of its superiority in terms of harmonic distortion, switching losses and utilization of direct current (DC) bus. The synchronization is achieved by using second order generalized integrator (SOGI) due to its simple structure, certain filtering ability and frequency adaptability, in which the phase locked loop (PLL) ensures high performance for single-phase inverter. The active and reactive inverter current has been controlled and decoupled from each other and the dynamic response has been improved and became fast with proper feed-forward and decoupling grid voltage term. The system has simulated by MATLAB and the result shows robust control of injected grid current, active and reactive power control and DC link voltage control.